2023
DOI: 10.1002/ajoc.202200662
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Aluminate Induced Pt(0)‐Pt(δ+) Coupling Boost Catalyzed H−D Exchange Reaction of Arenes with Deuterium Oxide

Abstract: Deuterium(D)‐labeled aromatics play an essential part in the Yield of fine chemicals. However, deuteration reactions are particularly dependent on the specific chemical environment of the metal to finish the oxidative addition and reductive elimination. Herein, a complex valence Pt/Ca12Al14Ox catalyst was successfully synthesized for the deuteration of toluene using inexpensive D2O. It exhibited high deuteration efficiency, achieving 96% deuteration in just 4 hours, 14% higher than the most commonly Pt/C catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 84 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…The electronegativity of O and P directly affects the electronic structure of Ru, which is induced to a low oxidation state. The low oxidation state metal will perform the oxidative addition and reductive elimination reactions more effectively. , Due to the higher reactivity of the amino α-H compared to other positions, the relatively less electronegative P-modified Ru/NPC-800 catalyst exhibits better regioselectivity. To investigate the catalytic effect of the unique electronic structures of Ru modified by P and O on H atoms at different positions of 1,6-hexamethylenediamine, the deuterium incorporation rate and selectivity catalyzed by Ru/NPC-600 and Ru/NPC-800 catalysts were analyzed.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The electronegativity of O and P directly affects the electronic structure of Ru, which is induced to a low oxidation state. The low oxidation state metal will perform the oxidative addition and reductive elimination reactions more effectively. , Due to the higher reactivity of the amino α-H compared to other positions, the relatively less electronegative P-modified Ru/NPC-800 catalyst exhibits better regioselectivity. To investigate the catalytic effect of the unique electronic structures of Ru modified by P and O on H atoms at different positions of 1,6-hexamethylenediamine, the deuterium incorporation rate and selectivity catalyzed by Ru/NPC-600 and Ru/NPC-800 catalysts were analyzed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Most studies have revealed the catalytic performance of the metal catalysts in the HIE reaction such as Pt/C, Ir/C, and Ru/C. , The reduction state metal which undergoes high-temperature reduction and is absorbed by H 2 and D 2 O can effectively activate C–H bonds through the oxidative addition process, forming a metal intermediate, and generate deuterium-labeled products through reductive elimination processes. ,, Apart from the reduction state metal, low oxidation state metals are also capable of activating C–H bonds, thus enhancing the crucial oxidative addition and reductive elimination processes in the H–D exchange reactions. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research serves as a valuable source of inspiration for our study 1,2 . Regarding the investigation of metal‐support interactions, Pt/Ca 12 Al 14 O x catalysts have been employed to enhance deuteration efficiency in the HIE reaction 42 . However, hydrogen gas or donors remained necessary in these systems, as the necessity of hydrogen gas participation has been demonstrated by Sajiki et al, 43 posing challenges for substrates with sensitive functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Regarding the investigation of metal-support interactions, Pt/Ca 12 Al 14 O x catalysts have been employed to enhance deuteration efficiency in the HIE reaction. 42 However, hydrogen gas or donors remained necessary in these systems, as the necessity of hydrogen gas participation has been demonstrated by Sajiki et al, 43 posing challenges for substrates with sensitive functional groups. Hence, developing new catalysts suitable for hydrogen/deuterium exchange reactions, especially with sensitive substrates, is a prominent research focus.…”
mentioning
confidence: 99%